2012
DOI: 10.1074/jbc.m111.317131
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 Receptor-2 Promotes Invasiveness and Metastasis of Ovarian Cancer Cells through Signal Transducer and Activator of Transcription 3 (STAT3)-dependent Up-regulation of Matrix Metalloproteinase 2

Abstract: Background:The molecular mechanisms regulating the invasive and metastatic phenotypes of ovarian cancer cells are poorly understood. Results: BLT2 regulates invasion and metastasis of ovarian cancer cells through modulation of NOX4-ROS-STAT3-MMP2 axis. Conclusion: BLT2 is overexpressed in ovarian cancer cells and is critical for the invasiveness and metastasis. Significance: Our findings suggest BLT2 as a therapeutic target in ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 48 publications
2
57
0
Order By: Relevance
“…However, recent studies have suggested that BLT2 plays a role in cancer progression [12-15, 20, 23]. Previously, BLT2 has been shown to be increased in ovarian, bladder, and prostate cancers, and elevated BLT2 levels have been associated with cancer cell survival, chemoresistance and metastasis [20, 21, 38, 39]. In the present study, we found that LPS upregulated BLT2 in aggressive breast cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, recent studies have suggested that BLT2 plays a role in cancer progression [12-15, 20, 23]. Previously, BLT2 has been shown to be increased in ovarian, bladder, and prostate cancers, and elevated BLT2 levels have been associated with cancer cell survival, chemoresistance and metastasis [20, 21, 38, 39]. In the present study, we found that LPS upregulated BLT2 in aggressive breast cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…An increased abundance of LTB 4 and BLT2 has been observed in many types of tumors, including neuroblastomas, as well as pancreatic, bladder, breast and ovarian cancers [12-14, 18, 19]. In addition, a BLT2 inhibition reduced the incidence of metastasis in an in vivo mouse model [19-21]. Despite of these potential properties of BLT2 as a pro-tumorigenic mediator, its role in LPS-driven cancer potentiation has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of leukotriene B 4 (LTB 4 ), one of the local lipid mediators in the inflammatory microenvironment, and its receptor, BLT2, are markedly up-regulated by oncogenic Ras and mediate Ras-associated tumorigenic activities (10 -12). Expression of BLT2 in ovarian and breast cancer tissue is increased in advanced stages and is associated with poor clinical outcome (13)(14)(15). Furthermore, autocrine or paracrine BLT2 signaling mediates the invasiveness and metastasis of ovarian, bladder, and breast cancer cells (14,16,17).…”
mentioning
confidence: 99%
“…These results are in line with previous studies in other cell models demonstrating that STAT3 seems to be involved in the LIF-induced MMP release; for example, in fibroblasts it activates MMP-9 release (Wang et al 2007). In ovarian cancer cells, inhibition of STAT3 led to a decrease in MMP-2 activity in cell culture supernatant (Seo et al 2012). Additional LIF could not reverse the effects of STAT3 inhibition on MMP-2 and MMP-9 expression.…”
Section: Discussionmentioning
confidence: 87%